5x+-5.2=9.4+3x

Simple and best practice solution for 5x+-5.2=9.4+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+-5.2=9.4+3x equation:



5x+-5.2=9.4+3x
We move all terms to the left:
5x+-5.2-(9.4+3x)=0
We add all the numbers together, and all the variables
5x-(3x+9.4)-5.2+=0
We add all the numbers together, and all the variables
5x-(3x+9.4)=0
We get rid of parentheses
5x-3x-9.4=0
We add all the numbers together, and all the variables
2x-9.4=0
We move all terms containing x to the left, all other terms to the right
2x=9.4
x=9.4/2
x=4+1/1.42857142857

See similar equations:

| 7+7u=4+6u | | 6-(4x-7)=6-5x | | -4+y/5=9 | | 2+2z=7z-8 | | 8(x+3)=-16 | | -9-u=7-5u | | 5y^2+44y+46=0 | | 20-8x=15=x | | 360=35+35+x+x | | -3=12y-512y-7 | | -2-9w=-8w | | 2x+3x-1=5x-1 | | .08x+x=252 | | 2.5x-8=1.5x+1 | | 7f=8+8f | | 5=-2-(1/x) | | 8r+2=72+r | | 13+6t=9 | | -8r=-10-7r | | 5g=6g-7 | | 6y+22=3y+49 | | 12r+12=3r+84 | | 12x+4x-9=9x+7-5x | | 3a-5=a-7 | | -x+4+3x=2x | | 9x-x+2=10 | | -5z-9=6z | | 5+8(x+8)=69-12(3x+11) | | 5+2x=200 | | -33z=26z | | 5b+9+16=-2. | | 3x-14=x+90 |

Equations solver categories